2022
DOI: 10.1097/gox.0000000000004671
|View full text |Cite
|
Sign up to set email alerts
|

Power-assisted Liposuction for Lymphedema: A Cost-utility Analysis

Abstract: Background: Lymphedema is a chronic, debilitating disease that has been described as the largest breast cancer survivorship burden. Debulking surgery has been shown to improve extremity volume, improve patient quality of life, and decrease the incidence of cellulitis in the literature. This procedure is routinely covered in numerous other developed countries, yet it is still inconsistently covered in the United States. Methods: Extremity volumes from al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…30 Bloom et al estimated a lifetime out-of-pocket cost of $83,240 for compression garments and physical therapy as conservative lymphedema management. 31 A handful of studies have investigated the economic utility of ILR specifically. Squitieri et al found that ILR is economically preferred over mastectomy and ALND alone from a cost minimization perspective, and results in an average of $7646.65 (45.2%) cost saving per patient over the course of their lifetime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Bloom et al estimated a lifetime out-of-pocket cost of $83,240 for compression garments and physical therapy as conservative lymphedema management. 31 A handful of studies have investigated the economic utility of ILR specifically. Squitieri et al found that ILR is economically preferred over mastectomy and ALND alone from a cost minimization perspective, and results in an average of $7646.65 (45.2%) cost saving per patient over the course of their lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that among breast cancer patients, those who develop BCRL incur significantly higher costs associated with their care ($86 707 vs. $64,554, p = 0.0002), including mental health services, diagnostic imaging, and complex outpatient visits 30 . Bloom et al estimated a lifetime out‐of‐pocket cost of $83,240 for compression garments and physical therapy as conservative lymphedema management 31 . A handful of studies have investigated the economic utility of ILR specifically.…”
Section: Discussionmentioning
confidence: 99%
“…The model adopted the perspective of the third-party payer, which has been well described in the literature. [16][17][18][19][20] We used publicly available cost data from 2023 Medicare current procedure terminology (CPT) codes and diagnosis-related group (DRG) codes. Direct surgical costs of both procedures, as well as associated costs of each health state, were reported in US$2023 (Table 1).…”
Section: Costs and Perspectivementioning
confidence: 99%
“…24 Although compression therapy remains widely used, surgical interventions offer cost-effective options and hope for improved outcomes and quality of life. [24][25][26][27] Despite the emergence of effective lymphatic reconstruction techniques more than 15 years ago, many patients are never offered treatment due to inaccessibility of care. 28 While public and insurance policy attempt to maintain pace with standard surgical practices, the absence of specific Current Procedural Terminology (CPT) codes to describe lymphatic reconstruction may pose a barrier to insurance authorization and ultimately surgical treatment.…”
mentioning
confidence: 99%
“…Combining physiologic microsurgical procedures (LVB or VLNT) with liposuction has consistently enhanced outcomes, reducing the need for lifelong compression garment use 24 . Although compression therapy remains widely used, surgical interventions offer cost-effective options and hope for improved outcomes and quality of life 24–27 …”
mentioning
confidence: 99%